Amoral Animal Rights (trans. D. Chabrajska) - MAKRS, Joel; CHABRAJSKA, Dorota (Katolicki Uniwersytet Lubelski Jana Pawła II, 2020)
The study of nonhuman animals has proved to be in my own life not only an important topic in its own right but also the undoing of all of my normative commitments and indeed of normativity (of the moralist stripe) itself. This evolution has taken two interesting turns. The first was my sense that animal ethics should be understood not only as a branch of applied ethics but also as integral to ethics as such. Animal ethics speaks to the very nature of ethics; ethics might even itself be better understood as s y n o n y m o u s with animal ethics, since human beings are themselves animals and may be ethical beings in virtue of that fact. The second turn was the realization that ethics may be better understood as about desire than about obligation (or morality or right and wrong or inherent value or justification, etc.). This turn did not come about by purely meta-ethical thought but, in equal measure, was midwifed by my growing awareness that the human moral response to the plight of other animals at human hands was a sham. Thus, I ended up facing the philosophical (and personal) challenge of my career and life: How to reconcile two apparently diametrically opposed facts, namely, the amoral basis of ethics and my personal commitment to animal liberation. This essay presents my response to that challenge. W moim życiu kwestia bytów ożywionych innych niż człowiek nie tylko okazała się ważna sama w sobie, ale również doprowadziła mnie do anulowania wszystkich moich osobistych przekonań moralnych, a w istocie całego pojęcia normatywności (w sensie moralnym). W trakcie tej ewolucji zaszły dwa interesujące zwroty. Pierwszy miał miejsce, kiedy zacząłem żywić przekonanie, że etykę postępowania wobec zwierząt należy traktować nie tylko jako gałąź etyki stosowanej, ale jako integralny element etyki jako takiej. Etyka postępowania wobec zwierząt sięga bowiem samej istoty etyki; etykę jako taką można by lepiej pojmować, gdyby była ona utożsamiana z etyką postępowania wobec bytów ożywionych, ponieważ sami ludzie są bytami ...